Research of Accounting and Control Support for Equity Management of a Commercial Company - D. A. Lavrov (Учёт. Анализ. Аудит)
The efficiency of equity management of any commercial organization largely depends on the information generated within its accounting and control system (ACS). The paper describes the study of accounting and control support for managing a company’s equity capital. The theoretical and methodological basis of the study bottoms on works of scientists in the researching scape, regulatory legal acts on accounting and auditing in the Russian Federation. The work clarifies the conceptual apparatus, an interrelation the notions as ‘accounting and control support’ and ‘accounting and control system’; founds a place of the last notion in the system of information management of a commercial company as well as the author defines the concept of ‘accounting and control support of equity capital management’. Moreover, there have been identified factors affecting the set of specific tools which have been using in the accounting and control system of each commercial company. The main results of the study can be used by chief accountants and auditors in the development and improvement of accounting and internal control system of a commercial company.